Puerperal Tetanus in Water Buffalo – A Case Report - Boora, A.K.; Yadav, S.; Jain, V.K.; Rana, N.; Singh, K.P.; Balhara, A.K. (Journal of Buffalo Science, 2013)
Reports of tetanus in buffaloes are scanty in comparison to cattle, horse, sheep and goat. A six years old Murrah buffalo, five days post-partum, was presented for treatment with a history of manual removal of retained placenta. Prolapse of third eyelid, complete locking of jaw, development of curve in spine, erection of ear and typical “pump-handle” position of tail were visible signs. Diagnosis was established on the basis of case history and clinical signs. Treatment was carried out with irrigation of genital tract with 3% solution of hydrogen peroxide and administration of hypertonic saline solution (7.5%), dextrose normal saline (5%), penicillin G procaine in high dose, ketoprofen and chlorpromazine. The animal fell like a stiff, wooden structure on day 11 of the onset of the disease and succumbed to its illness.